Persuasive multimedia model in truancy awareness (PMTA) - Lufti, Dolhalit (2019)
Persuasive multimedia is a research related to the use of multimedia to persuade for positive change in attitudes and behaviours. In the issues of truancy, its shows that, students who do not have awareness will involve in truancy problem. In addition, many academic researches appeared to focus on causal factor related to truancy rather than enhancement of awareness towards truancy behaviour. On the contrary, with so much emphasis placed on the use of multimedia material in schools, it is surprisingly found, very little indication exists in using multimedia as an approach for truancy awareness. Previous finding reveals that, there is a lack of design model and methods that systematically tailor the crucial theories, component, and strategies in the development of persuasive multimedia for truancy awareness. Within this context, the main purpose of this study is to propose a persuasive multimedia model in truancy awareness (PMTA) for secondary school students. This model serves as systematic approach, which includes fundamental components for developers to develop truancy awareness application. Therefore, in order to accomplish the main objective, a number of sub objectives are formed: (1). To determine the suitable persuasive multimedia components and elements for PMTA model development, (2). To formulate a persuasive multimedia model in truancy awareness (PMTA), (3). To validate the PMTA model through expert review and prototyping, and (4) To assess student’s perceived truancy awareness of the PMTA model through prototyping. This study adopts the Design Science Research (DSG) methodology as the framework of the research process. In achieving objective (1) and (2), a literature review and comparative analysis were conducted. Whereas for objective (3) and (4) it was achieved through expert review and experimental testing. There are four major contributions of this study: (i). PMTA model development, which comprises the guideline for developing persuasive multimedia content, (ii). Q-PMTA instrument to measure student’s perceived awareness, (iii). Functional PMTA prototype to validate the PMTA model and (iv). Experimental testing results to measure perceived truancy awareness. Findings demonstrate that the PMTA model exhibits useful development for multimedia application as well as providing theoretical and practical contributions of the study.In conclusion, the adoption of PMTA model provides guidelines for developing persuasive multimedia content to promote truancy awareness and contribute to enhance the learning experience towards truancy awareness.